1988
DOI: 10.1152/jn.1988.60.4.1303
|View full text |Cite
|
Sign up to set email alerts
|

Sensory inputs from the oral region to the cerebral cortex in behaving rats: an analysis of unit responses in cortical somatosensory and taste areas during ingestive behavior

Abstract: 1. The responses of 90 cortical neurons in the somatosensory and gustatory areas were recorded with chronically implanted fine wires in freely moving Wistar rats. The responses were analyzed mainly while the animals were freely licking solutions and eating dry pellets. Cortical neurons were classified into several groups according to their response properties. 2. "Mechanosensitive" neurons (n = 20) showed rhythmic phasic activity in different phases of the licking cycle, depending on the location of their rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 0 publications
5
48
0
Order By: Relevance
“…Yamamoto et al (47) reported that in the rat a subset of neurons in the insular cortex (IC) responds to mechanical stimulation of oral structures. In agreement with this study, a functional magnetic resonance imaging (fMRI) study of humans reported activation of the IC and supplementary motor cortex during vibratory stimulation of teeth (48).…”
Section: Cortical Responses To Pdl Stimulationmentioning
confidence: 99%
“…Yamamoto et al (47) reported that in the rat a subset of neurons in the insular cortex (IC) responds to mechanical stimulation of oral structures. In agreement with this study, a functional magnetic resonance imaging (fMRI) study of humans reported activation of the IC and supplementary motor cortex during vibratory stimulation of teeth (48).…”
Section: Cortical Responses To Pdl Stimulationmentioning
confidence: 99%
“…Some neurons in GC respond to somatosensory stimulation of the tongue and oral cavity (Yamamoto et al, 1988). These neurons fire action potentials synchronized to the rhythmic (6 -9 Hz) licking behavior produced by the rat during taste sampling (Katz et al, 2001a).…”
Section: Detection Of Lick-rate Modulation In Somatosensory Neuronsmentioning
confidence: 99%
“…In the insular cortex, a variety of neurons that respond to taste, tactile, thermal, or nociceptive stimulation (Cechetto and Saper, 1987;Yamamoto et al, 1988;Allen et al, 1991;Hanamori et al, 1998) were layer-specifically distributed. Tasteresponsive neurons together with low-threshold mechanoreceptive and wide-dynamic range neurons were mainly identified in layer V, whereas nociceptive-specific neurons were in layer II/III (Wang and Ogawa, 2002).…”
Section: The Functional Significance Of Columnar Organization In the mentioning
confidence: 99%
“…Indeed, there were considerable overlaps among the representation areas of the four basic tastes in rats (Accolla et al, 2007). The taste neurons are intermingled with sensory neurons for various other modalities such as tactile, thermal, and nociceptive sensations (Cechetto and Saper, 1987;Yamamoto et al, 1988;Allen et al, 1991;Hanamori et al, 1998). Furthermore, the gustatory insular cortex is mainly composed of dysgranular and agranular cortices, thereby displaying either a thin layer IV or no layer IV (Yamamoto et al, 1984).…”
Section: Introductionmentioning
confidence: 99%